Reliability Study of the PVGIS Database and the Simple ClearSky Model in Estimating Daily Horizontal Solar Radiation (GHI): A Case Study – Tajoura (Journal of Technology Research, 2025)
Photovoltaic (PV) systems have reached high efficiency and grid parity in many regions, yet their performance often remains suboptimal due to inappropriate design practices and inconsistencies in system components. Accurate solar radiation data are essential for evaluating PV performance, as on site measurements provide the highest reliability. However, when such data are unavailable, mathematical models and satellite databases are used despite their lower accuracy and the uncertainty they introduce. This study assesses the reliability of the Clear-Sky model and the PVGIS database in estimating global horizontal irradiance (GHI) for the Tajoura region. Actual radiation data for 2021 were obtained from the monitoring station of the Libyan Center for Solar Energy Research and Studies and validated using the DQRs methodology. Annual daily radiation matrices for actual data, the Clear-Sky model, and PVGIS were generated using MATLAB and statistically compared. Results show that the Clear-Sky model produces acceptable annual estimates but consistently overestimates radiation, with rMAE = 12%, rRMSE = 18.1%, rMBE = +10.15%, R² = 0.84, and NSE = 0.75. PVGIS demonstrated higher accuracy, with moderate errors (5–7%), NSE = 0.96, a slight negative bias (MBE = –0.81%), and strong correlation with actual values (R² = 0.96). Although both tools are useful for monthly and annual assessments, caution is required when using them for daily or instantaneous forecasting due to increased uncertainty.
Keywords: Global Horizontal Irradiance; Clear-Sky Model; PVGIS; Solar Irradiation Data Analysis; Statistical metrics